(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In this study, we observed the phonetic variation of voiced bilabial occlusive phoneme in non-standard Spanish in a sample of Chilean speakers from cities whose geographical locations allow to cover the main urban sectors of the country. The results that show a marked use of voiced labiodental approximant allophone in this type of speech an a relatively homogenous behaviour in the whole country of the main variants of the voiced bilabial occlusive phoneme are presented. The comparison of voiced bilabial occlusive phoneme between non-standard and standard Spanish shows clear differences, data that suggest a linguistic change in process from voiced bilabial approximant allophone to voiced labiodental approximant allophone.